1995
DOI: 10.1073/pnas.92.2.566
|View full text |Cite
|
Sign up to set email alerts
|

Effect of erythrocyte membrane on extracellular development of the erythrocytic cycle of Plasmodium falciparum.

Abstract: We have earlier reported conditions that support the axenic development in vitro of a complete asexual erythrocytic cycle of Plasmodium fakciparum. Up to 30%o of merozoites showed initial differentiation into trophic forms (rings) viable at 14 hr. However, only -1% of the merozoites would develop further into trophozoites and early schizonts viable at 36 hr. In efforts to increase the number of late stage parasites, we have now found a significant favorable effect of the addition of erythrocyte ghosts. Doublin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…A protective effect against malaria infection is associated with inherited disorders in RBCs, such as cytoskeleton disorders, surface antigen gene mutations, enzymatic deficiencies or hemoglobin alterations 31 . Several earlier studies also reported the effect of erythrocyte membrane on the growth of malaria parasites 32 33 .…”
Section: Discussionmentioning
confidence: 90%
“…A protective effect against malaria infection is associated with inherited disorders in RBCs, such as cytoskeleton disorders, surface antigen gene mutations, enzymatic deficiencies or hemoglobin alterations 31 . Several earlier studies also reported the effect of erythrocyte membrane on the growth of malaria parasites 32 33 .…”
Section: Discussionmentioning
confidence: 90%
“…However, in vitro studies (Lecomte et al, 1991;Schulman et al, 1990) on the malarial infection of erythrocytes carrying genetically defined membrane abnormalities have shown the necessity of a qualitatively and quantitatively normal membrane skeleton for an efficient invasion and a complete maturation of the parasite. Studies of extracellular development of the erythrocyte cycle of Plasmodium falciparum have also shown that constituents of the erythrocyte membrane favour the development of rings into trophozoites and schizonts (Williams et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Trager et al (90) postulated that contact between parasite and spectrin in the erythrocyte sonicate may be an important factor for development. More recently, Williams et al (99) have increased the yields of schizonts forming extracellularly by addition of erythrocyte ghosts obtained by osmotic lysis, to double the amount of membrane present. These results support the critical role of the erythrocyte membrane in the development of the malarial parasite.…”
Section: Cell-free Development Of Erythrocytic Stagesmentioning
confidence: 99%